Copper-Doped Zinc Oxide Nanoparticles: Synthesis, Characterization, and Application for Adsorptive Removal of Toxic Azo Dye - Bandela Sowjanya; Pulipati King; Meena Vangalapati; Venkata Ratnam Myneni (International Journal of Chemical Engineering)
The goal of this research was to employ copper-doped zinc oxide nanoparticles (Cu/ZnONPs) as an adsorbent to remove the potentially toxic azo dye Congo red (CR). The Cu/ZnONPs were made using a chemical coprecipitation method, and their characteristics were examined using XRD, SEM, EDS, and FTIR methods. The response surface methodology (RSM) central composite design (CCD) is used to optimize the operational parameters’ agitation time, adsorbent dosage, solution pH, and initial concentration of CR solution during the adsorption process. The agitation period of 29.48 min, the Cu/ZnONP dosage of 0.301 g/L, the solution pH of 6.96, and the CR initial concentration of 90 mg/L resulted in a maximum CR adsorption of 94.14% and a desirability of 0.976. The kinetic findings fit the pseudo-second-order kinetic equation, and the equilibrium data agreed with the Langmuir isotherm (maximum uptake capacity qmax = 250 mg/g). During the thermodynamic experiments, endothermic, spontaneous, and physical adsorptions were observed.